2020
DOI: 10.1111/iju.14418
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference for urologist gender

Abstract: Objectives To determine the factors associated with patients preferring the gender of their treating urologist in various clinical settings. Methods A total of 400 urology outpatients participated in a structured interview on the nature of their presenting complaint, perception of their complaint and the preference for the gender of their urologist in four specific scenarios of consultation, physical examination, office‐based procedure and surgery. Patients who expressed a gender preference received follow‐up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Preferences for gender concordance were also seen in how most respondents reported that they felt more comfortable communicating with (67.6%) and being examined by (73.3%) surgeons of the same gender as themselves. In the West, gender concordance is more likely to be preferred only in surgical subspecialties that entail physical examinations of a sensitive nature, such as OBGYN, urology, or breast surgery [30][31][32][33][34][35]. However, even in these subspecialties, a sizeable percentage of patients in Western populations still report no gender preference [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preferences for gender concordance were also seen in how most respondents reported that they felt more comfortable communicating with (67.6%) and being examined by (73.3%) surgeons of the same gender as themselves. In the West, gender concordance is more likely to be preferred only in surgical subspecialties that entail physical examinations of a sensitive nature, such as OBGYN, urology, or breast surgery [30][31][32][33][34][35]. However, even in these subspecialties, a sizeable percentage of patients in Western populations still report no gender preference [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In the West, gender concordance is more likely to be preferred only in surgical subspecialties that entail physical examinations of a sensitive nature, such as OBGYN, urology, or breast surgery [30][31][32][33][34][35]. However, even in these subspecialties, a sizeable percentage of patients in Western populations still report no gender preference [34,35]. The preference for gender concordance across most surgical subspecialties in our population likely reflects conservative sociocultural elements within Pakistani society.…”
Section: Discussionmentioning
confidence: 99%
“…Although research has begun to increasingly focus on patient satisfaction, there is only limited knowledge on how patients choose their urologist and for gender preference. 4,5,[9][10][11][12] Recently, we could show that patients chose their urologist based on fairly rational grounds, focusing on certain core variables, such as professional skill and academic criteria of the urologist, or being attended by the same urologist at every visit, or by personal referral. 5 These findings were later corroborated with the European Association of Urology Section of Outpatient and Office Urology (ESUO) questionnaire by Zachariou, et al 4 Those studies included board certification as surrogate for professional skill, and academic degree as visible external factor for professional accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…Although research has begun to increasingly focus on patient satisfaction, there is only limited knowledge on how patients choose their urologist and on the impact of gender. 4,5,[9][10][11][12] Patients in the German healthcare system provide an ideal study cohort, as Germany has one of the most restrictionfree and consumer-oriented healthcare systems. Compared to other healthcare systems, in which insurance networks may greatly influence patients' choice of a urologist according to a particular healthcare plan or healthcare provider, as is often the case in the US, the German healthcare system allows patients to seek nearly any type of care they wish, and whenever they want it.…”
Section: Introductionmentioning
confidence: 99%